The day to day of an Education inspector - Carmen ROMERO UREÑA (Aula, 2019)
The article tries to collect a sample of actions that are carried out in the education inspection in three moments of the course, one day of each school term. It is written in the form of a life story because it aims to build the collective of this group of professionals that is so unknown and, at the same time, so fundamental to the education system. It is organized through three differentiated parts, the first is a brief foundation of the history of life framed in a perspective of qualitative research and through a biographical and narrative methodology; the second is the three-day account of the 2017/18 school year, which is peppered with reflections derived from the actions carried out and ends with a third part with some conclusions, the result of the daily experience of an education inspector.